2011
DOI: 10.4172/2161-1017.s2-001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hyperlipidemia and associated risk factors among healthy young Saudi females:relationship with waist Circumference and body Mass Index

Abstract: Background and Objectives: Hyperlipidemia, insulin resistance and hypoadiponectinemia are well recognized cardiovascular risk factors especially among obese subjects. The aim of the present study was to determine the prevalence of hyperlipidemia and associated risk factors among young Saudi females and their relationship with waist circumference (WC) and body mass index (BMI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, it should be noted that majority (57.8%) of the participants fall within the normal BMI range. Previous research has reported a growing prevalence of obesity among Saudi women [2], with Al Kadi and Alissa [16] reporting a high prevalence of overweight and obesity (20%). Another important finding of this study is that across all ages, in total, 21.1% of the participants were found to be pre-hypertensive, while 13.5% were pre-diabetic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that majority (57.8%) of the participants fall within the normal BMI range. Previous research has reported a growing prevalence of obesity among Saudi women [2], with Al Kadi and Alissa [16] reporting a high prevalence of overweight and obesity (20%). Another important finding of this study is that across all ages, in total, 21.1% of the participants were found to be pre-hypertensive, while 13.5% were pre-diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is worrisome as it has been reported that intra-abdominal fat has deleterious impact on metabolism [23]. Al Kadi and Alissa [16] stated that studies conducted in East Asian countries have regularly emphasized the necessity to decrease BMI and waist circumference cut-off points for assessing the risk of metabolic disorders. Therefore, follow-up evaluations of such participants in the present study including referral to their physicians should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…• Obesity: The prevalence of obesity [83] has markedly increased in most countries of the world. A positive association between obesity and the risk of developing type 2 diabetes [84] has been consistently observed in many populations.…”
Section: Signs Of Insulin Resistance Syndromementioning
confidence: 99%